2011
DOI: 10.1007/s11104-011-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting diurnal variations in soil organic carbon decomposition and root respiration due to a hysteresis effect with soil temperature in a Gossypium s. (cotton) plantation

Abstract: To understand the characteristics of the diurnal variation in soil respiration and its response to temperature, we used root exclusion plots, and buried CO 2 sensors in situ during the late growing season in northwestern China. Soil organic carbon (SOC) decomposition and root respiration dynamics were quantified. In our study, we found that the diurnal variations in root respiration and soil organic carbon (SOC) decomposition showed a contrasting diurnal pattern. SOC decomposition peaked in the afternoon and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Zhi-Min et al (2013) observed that the average contribution of root respiration to total soil respiration was about 32 %. Li et al (2011) pointed out mean contribution of root respiration to total soil respiration over 60 %. Another hypothesis may be related to the tendency to dissociate CO 2 to cause acidity in the soil and control the acidity potential, because the carbonic acid produced by dissolving CO 2 in water is an important acidifying agent in natural systems (Reuss and Johnson, 1986;Tossell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Zhi-Min et al (2013) observed that the average contribution of root respiration to total soil respiration was about 32 %. Li et al (2011) pointed out mean contribution of root respiration to total soil respiration over 60 %. Another hypothesis may be related to the tendency to dissociate CO 2 to cause acidity in the soil and control the acidity potential, because the carbonic acid produced by dissolving CO 2 in water is an important acidifying agent in natural systems (Reuss and Johnson, 1986;Tossell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased rainfall in arid and semiarid regions in northwestern China under future climate scenarios is expected to modify the Q 10 value (Curiel Yuste et al, 2003;LelleiKovacs et al, 2011;Jiang et al, 2013). Many experimental studies have investigated the response of daily Q 10 to rainfall variability (Liu et al, 2008;Zhang et al, 2010;Bowling et al, 2011;Li et al, 2011;Thomas et al, 2011;Shi et al, 2012;Vargas et al, 2012). However, we are not aware of any studies which distinguished the differential responses of daily Q 10 of R H and R A to rain change.…”
Section: Introductionmentioning
confidence: 99%
“…This 24-h variation was obtained in agro-ecosystems in a temperate climate (Shi et al, 2006), an arid climate (Li et al, 2011) and a Mediterranean climate (Xu and Qi, 2001). These authors explain this process as a function of soil temperature because this is a variable that changes considerably in the course of a day (Rayment and Jarvis, 2000).…”
Section: -H Variation Of Sr Soil Temperature and Moisturementioning
confidence: 97%